2015
DOI: 10.1080/10410236.2014.963786
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical information seeking amid conflicting health information: negative and positive effects on prostate cancer screening

Abstract: This study investigates the impact of seeking information about the prostate-specific antigen (PSA) test on men's PSA test use during a period of conflicting recommendations. Analyses used longitudinal survey data collected in 2005 and 2006 from a nationally representative sample of U.S. males aged 40 to 70 (n=777). Cross-sectionally, non-medical seeking was significantly associated with increased odds of having a PSA test in the past year (Time 1 OR=9.74, p < .01, 95% CI=4.37, 21.70; Time 2 OR=5.78, p < .01, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Men were predominantly active information‐seekers in 6 studies: 2 qualitative and 1 quantitative longitudinal study assessing information‐seeking for prostate cancer screening, 1 cross‐sectional and 1 qualitative study on general cancer information‐seeking, and 1 qualitative study on information‐seeking for skin cancer prevention …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Men were predominantly active information‐seekers in 6 studies: 2 qualitative and 1 quantitative longitudinal study assessing information‐seeking for prostate cancer screening, 1 cross‐sectional and 1 qualitative study on general cancer information‐seeking, and 1 qualitative study on information‐seeking for skin cancer prevention …”
Section: Resultsmentioning
confidence: 99%
“…It was found that women were more likely than men to seek information on skin cancer prevention by using the Internet (36.1% for men vs 24.7% for women; P = .004). Other than the Internet, 11% of participants in the longitudinal study by Gibson et al actively sought PSA testing information from nonmedical sources, including family, friends, and co‐workers . Hicks et al also found that men's social networks were identified as important sources of information, while the participants in the study by Biddle et al actively sought PSA testing information from “medical journals, newspapers, television, media, chat rooms, and medical brochures” (p.6) as well as their family, friends, and men who had similar experiences …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have identified contradictory information about topics such as climate change (Nisbet, Hart, Myers, & Ellithorpe, 2013), cancer (Clarke & Everest, 2006; Smith, Kromm, & Klassen, 2010), and nutrition (Houn et al, 1995; Nagler, 2014) in the media. Both quantitative and qualitative studies have found that people perceive conflict about these and other topics (Carpenter, Elstad, Blalock, & DeVellis, 2014; Vardeman & Aldoory, 2008), which may drive them to seek more information (Weeks, Friedenberg, Southwell, & Slater, 2012) and influence their behavior decisions (Gibson et al, 2015). Yet few studies have explicitly assessed media exposure to contradictory information (Nagler, 2014; Nagler & Hornik, 2012; Tan, Lee, & Bigman, 2015), and research examining the effects of such exposure is limited (Chang, 2013, 2015; Dixon & Clarke, 2012; Jensen & Hurley, 2012; Nan & Daily, 2015).…”
mentioning
confidence: 99%
“…During our forum, AA community members expressed concerns about differing opinions they received from different PCPs. Conflicting recommendations from PCPs combined with confusing PrCA screening information available in the media [25] can lead to difficulty in making decisions regarding screening. Decision aids and education are shown to help AA men evaluate different opinions from PCPs based on their own condition, values, preferences, and goals [26].…”
Section: Discussionmentioning
confidence: 99%